Pola Komunikasi Konselor dan Narapidana - Arif Wibawa; Yenni Sri Utami; Siti Fathonah (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2016)
This study aims to find an effective communication model counselor in Narcotics Prison of Class IIA Sleman Yogyakarta in rehabilitating drug users. This study uses qualitative method for its ability to help clarify the picture of the development of models of effective communication patterns counselor Narcotics Prison Class II A Sleman Yogyakarta in rehabilitating drug users. The research found that the pattern of communication and coaching in the rehabilitation of drug users in Narcotic Prison of Class II A Sleman Yogyakarta consists of two patterns. The first is informal and formal communication patterns. The second concept is carried out by community terapeutic concept, a method aimed for the social rehabilitation for victims of drug users. This patterns aimed at forming prisoners in to a human who returned intact after dependence on drugs, fostering awareness of the law, reintegration in to society, job skills training, and counseling and rehabilitation programs.